Business Plan Project: A Step-by-Step Guide to Writing a Business Plan - Sellars, David (Business Expert, 2012)
Business Plan Project provides detailed instructions on how to write a comprehensive business plan for new ventures. The intended market segments are graduate or upper-level undergraduate students, entrepreneurs, consultants, and college instructors or corporate trainers. Business Plan Project can be used in executive development programs and over 10 collegelevel courses. Business Plan Project is designed to meet important needs of each segment: (1) the business plan serves as a means for college students to learn about the major functions of business and how they are interrelated, (2) entrepreneurs need a business plan to provide direction in the organization and launch of a new business and secure initial capital from funding sources, (3) consultants need a user-friendly business plan format to assist clients that have limited or no business experience, and (4) instructors and trainers need a turn-key text with supplements that require no lecture and little prep time to teach students how to write a business plan. Business Plan Project is a real-world, hands-on, step-by-step guide where students or entrepreneurs develop business plans for new ventures. The experience begins with brainstorming and deciding on a new business that meets the unique needs in the marketplace. It ends with writing a comprehensive business plan and conducting a PowerPoint presentation of the plan. Further realism is achieved through the use of a continuing case: AVID SPORTS, INC., a start-up company that plans to launch a high performance running shoe called “Propell.” All concepts in the text are explained using AVID as an example. The instructor’s manual includes outcomes for the learning experience, assessment methods, lesson plans, teaching ideas, test bank, fi nancial statement worksheets, and forms to grade the written plan and oral presentation of the plan. Since all information that students need to develop professional business plans is in the text, lectures, handouts, and other learning aids are optional. The instructor’s role can be that of a consultant to students. Business Plan Project has been thoroughly tested by students and entrepreneurs and can be offered as an e-book for domestic and international markets.